Aspects of Johannine Spirituality as it is Reflected in 1 John - Watt, Jan G. van der (Studies in Spirituality, 2012)
The focus of this article is on spirituality as it is expressed in 1 John. Since 1 John was written as reaction to a schism, the identity of the remaining group rests on their experience of being the people of the truth as it is expressed in their tradition and is evidenced in the presence of the Spirit among them. The opponents have abandoned both the tradition and Spirit and does not display true spirituality. It is argued that through proper discernment believers remain in God by remaining in his word through the guidance of the Spirit. In this way the author envisages the transcendental reality becoming part of the human reality thus leading to true spirituality.
free